The first step in the functional inactivation of the Escherichia coli polynucleotide phosphorylase messenger is a ribonuclease III processing at the 5' end. - Portier, C (1987)
The transcripts covering pnp, the gene encoding polynucleotide phosphorylase, are processed by ribonuclease III. In this study, it is shown that the steady state level of the pnp mRNA increased 11-fold in a ribonuclease III-deficient strain. The synthesis rate of this messenger is only slightly affected in the mutant strain whereas the half-life, which is 1.5 min in the wild type, is considerably increased to more than 40 min. Moreover, polynucleotide phosphorylase is 10-fold over-expressed in the mutant strain, which shows that unprocessed pnp mRNA is functional. The position of the ribonuclease III-sensitive site suggests that the sequence involved in the stabilization of the pnp mRNA is located at the 5' end of the message and that the RNase III processing triggers the decay of the transcripts downstream. A similar function for ribonuclease III in the processing of the messenger for the beta beta' subunits of RNA polymerase is proposed.